The Phenomenon of BUMN Employee Recruıtment In Indonesıa: Advanced Development of Talent Management Research Trends 2018 – 2021 and Career Development - Putra Satriya Yudha; Rr. Sri Handari Wahyuningsih; Retno Widowati (APMBA (Asia Pacific Management and Business Application), 2023)
This study is a meta-analysis of research that has already been done by other writers. In bibliometric analysis, researchers use the findings of earlier study to identify trends in the field. In this study, the outcomes of this research trend were developed and honed to be more precise. This research uses SNA (Social Network Analysis) with the social media X database or what we know as Twitter as the data source. The data obtained was 225, which were then processed using NVivo12. Researchers use word clouds to identify possible themes, especially in the early stages of a project and Analyze the most frequently used words within a particular demographic. Next, classify it into four sections: originality of content, manipulated content, and positive and negative opinions.